Three-dimensional elasticity solution for sandwich panels with corrugated cores by using energy method. (October 2017) - Shaban, M.; Alibeigloo, A.
Abstract: Sandwich panels having metallic corrugated cores extremely utilized in various engineering fields such as aerospace, automotive, civil, and naval engineering. Although significant efforts have been dedicated in research into corrugated sandwich panels, analytical solutions are still very few. In this paper, analysis of corrugated sandwich panels with trapezoidal shape is carried out analytically. In the present study, a new analytical approach is developed for bending analysis of corrugated sandwich panels which have not been considered yet. The out-of-plane properties of corrugated core are obtained based on three dimensional theory of elasticity. The state-space method is implemented in conjunction with double Fourier series to solve the coupled partial differential equations. To validate the present approach, numerical results are compared with the results reported in the literature. The sensitivity analysis of the stress and displacement components to the geometrical parameters of corrugated core and its orthotropy is presented by introducing dimensionless ratios. Highlights: Using three-dimensional elasticity theory which is more reliable and accurate. Implementing the energy method in thickness direction and presenting equivalent orthotropic properties. Solving set of coupled equations analytically by using state-space approach. Providing an improved representation of bending behavior for finite length corrugated sandwich panels.